FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJAAN KETINGGIAN DI PT. X - Radita Mahendra; Bina Kurniawan; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2017)
Based on statistics in Indonesia, 80% of accidents caused by unsafe acts (substandard acts) and 20% by unsafe conditions (substandard condition).  Someone who works at a height of about 1.8 meters or more are included working at height activity. Approximately 80% of workers in the PT X project when working at heights do not use personal protective equipment properly.. This study aims to determine the worker's behavior towards the use of PPE when working at height. This research was a descriptive qualitative in-depth interviews. The subjects of this study amounted to five people as the main informant and two as an informant triangulation. The results showed four key informants in general already have a good knowledge of PPE and just 1 informant who did not have knowledge well. Key informants attitude submissived and obedient to wear PPE when reprimanded by the supervisor HSE. Key informants felt uncomfortable when wearing PPE. Key informant had indifferent attitude towards other workers. APD was always socialized with both oral and print media. PT X provides a complete and adequate PPE. Supervision runs regularly and was done by walking around the project area. Key informant's behavior towards the use of PPE in height already understood the importance of using PPE, but because using PPE uncomfortable Key informants sometimes did not use completely. PT X need to improve supervision on the use of PPE in cooperation with the security guard and the need to foster a culture of safety to workers.